Assessing the efficacy of a single‐unit red blood cell transfusion policy at a multisite transfusion service using a computerized retrospective audit. (19th July 2016) - Covello, T. P. C.; Quinn, J. G.; Kumar‐Misir, A.; Watson, S.; Almohammadi, M.; Crocker, B. D.; Conrad, D. M.; Tennankore, K.; Sadek, I.; Kahwash, E.; Cheng, C. K.
Abstract : Background and Objectives: In 2013, an Eastern Canada blood bank implemented a new policy to reduce red cell transfusion. The policy mandated clinical or laboratory reassessment of stable, non‐bleeding patients after each unit transfused, before issuing subsequent units. A computerized audit assessed the policy's effectiveness. Materials and Methods: This retrospective cohort study compares the policy's effect on transfusion practice across three groups of adult inpatients: haematology, surgery and internal medicine. Compliance was inferred from increases in the proportion of single‐unit red cell transfusions among all single‐ and double‐unit transfusions. Outcome variables included transfusion intensity (red cell units administered per admission involving a transfusion) and pretransfusion haemoglobin levels. Results: Each group had more transfusions issued as single units during the ten months following policy enforcement. In haematology patients, single‐unit transfusions increased from 17% to 89% and transfusion intensity decreased (median: 2–2, Q1: 2–1, Q3: 6–4, P < 0·001). Single‐unit transfusions increased from 57% to 94% in medicine patients and from 63% to 87% in surgery patients. Transfusion intensity also decreased in surgical patients (median: 2–1, Q1: 1–1, Q3: 2–2, P < 0·001) and in medicine patients (median: 2–1, Q1: 1–1, Q3: 2–2, P = 0·008). No group showed a clinically significant change in pretransfusion haemoglobin levels. Conclusion: The audit demonstrated significant compliance with a single‐unit transfusion policy. Transfusion intensity decreased in all groups despite no clinically significant change in pretransfusion haemoglobin levels.